2022
DOI: 10.1039/d1lc01068a
|View full text |Cite
|
Sign up to set email alerts
|

Portable sample processing for molecular assays: application to Zika virus diagnostics

Abstract: A digital microfluidic system was developed for portable Zika virus diagnosis, featuring integrated, automated sample extraction and amplification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 55 publications
0
29
0
Order By: Relevance
“…The open-source DropBot 38 control system used here was modified to include two automated heating units – an auxiliary heating unit (introduced here for the first time) was used to denature the sample at 70 °C during disulfide reduction by exposure to TCEP (Fig. 3d), and an integrated unit (reported previously 48,49 ) was used to incubate the sample at 37 °C during enzymatic digestion by exposure to trypsin, after an alkylation reaction by exposure to IAA (Fig. 3e), both programmed by the user and controlled by pulse-width modulation (PWM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The open-source DropBot 38 control system used here was modified to include two automated heating units – an auxiliary heating unit (introduced here for the first time) was used to denature the sample at 70 °C during disulfide reduction by exposure to TCEP (Fig. 3d), and an integrated unit (reported previously 48,49 ) was used to incubate the sample at 37 °C during enzymatic digestion by exposure to trypsin, after an alkylation reaction by exposure to IAA (Fig. 3e), both programmed by the user and controlled by pulse-width modulation (PWM).…”
Section: Resultsmentioning
confidence: 99%
“…Devices were controlled by using a custom version of the open-source DropBot system 38 (version 3.0, https://github.com/ sci-bots/dropbot-v3). 48,49 The DropBot and the built-in heater unit were controlled using a custom version of MicroDrop soware (version 2.31.1, https://github.com/sci-bots/ microdrop), while the auxiliary unit was controlled by a separate interface (in-house soware, written in Python). Devices were interfaced to the DropBot system through a pogopin connector, and electrodes were actuated in preprogrammed steps which allowed droplet dispensing, moving, and mixing by applying (typically) 100 V RMS as square waves at 10 kHz (parameters optimized as described below).…”
Section: Dmf Device Fabrication and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…88 Further, they demonstrated portable sample-processing DMF molecular assays for the detection of the Zika virus from a 5 μL sample using RNA captured on magnetic beads. 89 Oleschuk's group showed that the combination of lowfriction superhydrophobic surfaces and droplets containing superparamagnetic particles could reliably dispense droplets with high precision (≤6%). Droplets ranging in size from 5 to 20 μL were used for an EDTA-based on-chip complexometric colorimetric titration for water hardness.…”
Section: Magnetophoresismentioning
confidence: 99%
“…88 Further, they demonstrated portable sample-processing DMF molecular assays for the detection of the Zika virus from a 5 μL sample using RNA captured on magnetic beads. 89…”
Section: Application Of Magnetic Field-gradient Forcementioning
confidence: 99%